Ageing, impairments and travel: Priority setting for an inclusive transport system. (April 2018) - Martens, Karel
Abstract: The ageing of the population in many countries suggests that transport systems will have to be adapted to the needs of an increasing number of persons experiencing travel-related impairments. This development underscores the importance of a more fundamental challenge for transport planning: providing all persons with accessibility to key destinations, irrespective of the features of a person's body. The challenge is to move beyond the notion of universally accessible transport systems towards an inclusive transport system. Where the former focuses on adapting existing transport systems to the needs of persons with the widest possible range of abilities, the latter refers to the goal to provide all persons with access to a range of key destinations . This challenge requires not only the adaption of existing transport systems, but also the extension of those systems to provide travel-impaired persons and others with access to destinations. The aim of the paper is to develop a basic framework that can be helpful to set priorities towards the development of such an inclusive transport system. The framework distinguishes two principles for priority setting, one derived from the principle of welfare maximization and one conceptualizing the notion of hardship. Based on these two principles of priority setting, three different categories of measures to enhance accessibility for persons experiencing travel-related impairments are distinguished: (1) measures that live up to the principle of efficiency or welfare maximization; (2) measures that reduce transport-related hardship through adaptation or extension of the mainstream transport system; and (3) measures that reduce transport-related hardship through dedicated services for persons with travel impairments. The proposed framework requires changes in the practice of cost-benefit analysis, as well as a clear delineation of a hardship threshold. The latter is considered essential to make the transport problems experienced by persons with travel impairments visible to the public eye. Highlights: 6%–10% of population experiences some form of travel-related impairment. Shift from universally accessible transport to inclusive transport system needed. Framework for priority setting of measures is proposed to move to inclusive system. Framework encompasses the principles of welfare maximization and of hardship. Fundamental changes in cost-benefit analysis required to move to inclusive system.